Interventions for Communication and Language Development in Children with Autism Spectrum Disorder - Muhammad Fikri Pratama; Pramesti Pradna Paramita (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2023)
Communication and language are aspects that play a crucial role in a children's development. Autism spectrum disorder is a developmental disorder characterized by a lack of communication and language abilities in children. The prevalence of children with autism spectrum disorder is increasing every year, therefore early intervention is crucial. This study aims to describe the forms of intervention that can be implemented for children with autism spectrum disorder. The study used a literature review method in the form of journal articles from specific reference sources. The literature review yielded 15 journals relevant to the research topic, which is interventions that help in the development of communication and language skills in children in publications of at least the last 10 years. The forms of intervention identified are the picture exchange communication system, applied behavior analysis, visual media, developmental individual-differences relationship-based floortime, and storytelling. These forms of intervention can help children with autism spectrum disorder in developing their communication and language abilities